Financial inclusion and monetary policy in Nigeria: an analysis from 1993 to 2022 - Abdulmumin, Biliqees Ayoola; Adeoti, Oluwatosin Doris (Informe Econômico (UFPI), 2025)
Financial inclusion has been recognized across the globe as an essential factor for monetary policy to be more successful. Despite the Central Bank of Nigeria’s (CBN) efforts to establish an inclusive financial mechanism and effective monetary policy, many Nigerian adults remain financially excluded. This persists despite policies promoting digital financial services, agent networks, and mobile money, highlighting significant challenges to fully realizing the effectiveness of monetary policy in Nigeria. Thus, the research analyzed the financial inclusion and monetary policy in Nigeria from 1993 to 2022. Data were collected from CBN statistical bulletin and analyzed via Autoregressive Distributed Lag (ARDL) Model. The findings showed that financial inclusion variables had significant impact on monetary policy measures at 5% significant level. In light of the findings, the research concluded that financial inclusion had long run impact on monetary policy in Nigeria. The study suggested, amongst other, that commercial banks should increase their lending to small and medium scale enterprises to attract more small business into the financial mechanism and enhance effectiveness of monetary policy in the long run.